Penegakan Hukum Tindak Pidana Prosttusi Online Terhadap Pekerja Seks Komersial (PSK) Di Wilayah Hukum Polresta Padang - Sonia Permata Saria; Sry Wahyuni; Elwidarifa Marwenny (Jurnal Kajian Hukum Dan Kebijakan Publik | E-ISSN : 3031-8882, 2024)
The existence of prostitutes is undeniably growing in Padang city. There are many factors that lead a person to become a prostitute. Starting from economic demands, low levels of education, parental support, peer influence, domestic failure, and so on. Prostitution or prostitution is not considered a legitimate or legal occupation, but there are also those who continue to do it. The development of the times can change all forms of human activity, one of which is the existence of prostitutes in the city of Padang, no longer done by hanging out but with an online system using one of the applications, namely the michat application. The michat application is one of the instant messaging applications used on various cellphones. This application was originally created to help users communicate with friends and family. However, many people, especially in Indonesia, one of which is in the city of Padang, misuse this michat application as a means of online prostitution. Some of the cases that have been listed, online prostitution also occurs in the city of Padang which upholds religious values, namely adat basandi syarak, syarak basandi kitabullah. So it is necessary to conduct an in-depth study of the criminal act of online prostitution related to Commercial Sex Workers (PSK). Based on this description, the problems that the authors discuss in this thesis are (1) How is the law enforcement of online prostitution crimes against prostitutes in the Padang Police jurisdiction (2) What are the obstacles and challenges faced by the police in handling prostitution cases involving prostitutes. The method used in this research is qualitative with an empirical juridical approach. The conclusion that the author can get from the research is that law enforcement carried out by the Padang Police regarding online prostitution crimes against prostitutes is preventive and repressive. The obstacles and challenges of the police in handling cases involving prostitutes are network constraints, limited resources, changes in perpetrator tactics, the existence of perpetrators who are difficult to track, the development of digital platforms, lack of concrete evidence, and low reports.